Linking business analytics affordances to corporate strategic planning and decision making outcomes - Steffen Kurpiela; Frank Teuteberg (Information Systems and e-Business Management, 2023)
Business analytics is considered in research and practice as a promising approach to support organizations in the increasing complexity and dynamics in the strategic planning and decision making, which arise for example through the integration of product-service systems. However, literature is lacking a comprehensive analysis to what extant business analytics supports the strategic planning and decision making. Thus, coming from the affordance and socio-technical system theory, we are linking business analytics affordances to strategic planning outcomes. In doing so, we identified 20 affordances which we have assigned to the dimensions of the socio-technology system theory. Based on this, we have derived implications and propositions for research and practice. The results can be used as guidelines for practice and directions for future research.
Keywords: 650; Business analytics; Strategic planning outcomes; Affordance theory; Socio-technical system theory